Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fimmu.2021.620124
|View full text |Cite
|
Sign up to set email alerts
|

The “Gum–Gut” Axis in Inflammatory Bowel Diseases: A Hypothesis-Driven Review of Associations and Advances

Abstract: In modern medicine, the oral cavity has often been viewed as a passive conduit to the upper airways and gastrointestinal tract; however, its connection to the rest of the body has been increasingly explored over the last 40 years. For several diseases, the periodontium and gingiva are at the center of this oral-systemic link. Over 50 systemic conditions have been specifically associated with gingival and periodontal inflammation, including inflammatory bowel diseases (IBD), which have recently been elevated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 209 publications
(223 reference statements)
2
66
0
Order By: Relevance
“…The relative abundance of the genus uncultured_o_Absconditabacteriales (SR1) was lesser in yaks with supplementary concentrate feed than those without. Absconditabacteriales was linked with inflammatory bowel diseases [ 40 , 41 ] and periodontal diseases in humans [ 42 ]. In addition, Absconditabacteriales was associated with an unhealthy udder, and it was suggested that this genus could be used as a biomarker to assess mastitis in dairy cows [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of the genus uncultured_o_Absconditabacteriales (SR1) was lesser in yaks with supplementary concentrate feed than those without. Absconditabacteriales was linked with inflammatory bowel diseases [ 40 , 41 ] and periodontal diseases in humans [ 42 ]. In addition, Absconditabacteriales was associated with an unhealthy udder, and it was suggested that this genus could be used as a biomarker to assess mastitis in dairy cows [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These Th17 cells of oral origin can be activated by translocated oral pathobionts and cause the development of colitis when in the gut through IL-1β [22]. Indeed, Byrd et al [14] have hypothesized that IBD can be driven by microbiomial and inflammatory changes originating specifically from the gingival niche through saliva, thereby worsening IBD outcomes and thus perpetuating a vicious cycle. In fact, a recent scoping review has found that periodontitis and IBD patients share similarities in their microbiological and immunological patterns [23].…”
Section: Discussionmentioning
confidence: 99%
“…The persistence and dysregulation of the host immune and inflammatory responses are mainly responsible for the tissue destruction in both IBD and periodontal disease [12,13], and the inflammatory response activation might be the link between them [14]. In fact, the activity of IBD influences the inflammatory response not only in the intestinal tissue but also causes systemic inflammation as demonstrated by the higher levels of TNF-α and IL-17 in the blood of patients with IBD in comparison to patients without IBD or those in disease remission [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a bidirectional axis between the mouth and the gastrointestinal tract (GI) is not recent. In fact, possible relationships between the occurrence of pathologies of infectious origin in the oral cavity and inflammatory bowel disorders have been explored for decades ( 1 ). Both the oral tract and the GI tract deal with the external environment because of their vital epithelial barrier function in the digestive system, and such function depends on the interrelation between the host and the microorganisms to regulate either homeostatic balance or pathological instability.…”
Section: Anatomy Of Epithelia-malt In Oral and Gi Tractsmentioning
confidence: 99%